INTERSECTION OF LINGUISTIC AND CULTURAL WORLDS: BILINGUALISM IN THE NOVELS OF ABDELKEBIR KHATIBI (an analysis of Amour bilingue and La mémoire tatouée) - Nabiieva, Aziza (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2024)
The theme of bilingualism and cultural intersection in literature is highly relevant in today’s globalized world, where the processes of integration and interaction between different cultures and languages have become an integral part of daily life. These processes are particularly evident in the works of writers from countries with a colonial past. Studying their works provides a deeper understanding of how bilingualism and cultural blending influence literary self-expression, identity formation, and personal development. ______________ References: • Chmylenko, F. O. (2014). Posibnyk do vyvchennia dystsypliny "Metodolohiia ta orhanizatsiia naukovykh doslidzhen" [Manual for Studying the Discipline "Methodology and Organization of Scientific Research"]. DNU. • Stadnichenko, O. O. (2009). Osnovy naukovykh doslidzhen ta informatsiina kultura studentiv: navch. posibnyk [Fundamentals of Scientific Research and Information Culture of Students: Textbook]. Zaporizhzhia National University. • Khatibi, A. (1983). Amour bilingue. Denoël. • Khatibi, A. (1971). La mémoire tatouée. Denoël. • Medvid, V. (2020). Metodolohiia ta orhanizatsiia naukovykh doslidzhen (u strukturno-lohichnykh skhemakh i tablytsiakh): navch. posibnyk [Methodology and Organization of Scientific Research (in Structural-Logical Schemes and Tables): Textbook]. SNAU. • Kalambet, S. V. (2015). Metodoliia naukovykh doslidzhen: navch. posibnyk [Methodology of Scientific Research: Textbook]. Makovetsky Publishing House.